(untitled) (BIRDEM Medical Journal, 2021)
Background: Hematuria is one of the most common and early signs of diseases related to genitourinary system and can be classified as either glomerular or non-glomerular in origin. Percentage of dysmorphic RBC (%dRBC) in urine has been in practice as a diagnostic tool for differentiating glomerular from non-glomerular hematuria. Recent studies indicate that, urinary albumin-total protein ratio (uAPR) can also be used as a diagnostic tool in this regard. This study aimed to evaluate the sensitivity and specificity of uAPR as a diagnostic tool for detecting glomerular hematuria in comparison to %dRBC in urine. Methods: This cross-sectional study enrolled 96 patients with hematuria. Fresh urine samples were collected from each subject to determine the %dRBC and to calculate uAPR. Receiver operating characteristic curve analysis was done on these results to evaluate the sensitivity and specificity of uAPR and %dRBC in differentiating glomerular from non-glomerular hematuria. Results: uAPR and %dRBC were significantly (p<0.001) higher among patients with glomerular hematuria than non-glomerular hematuria. At the cutoff value of 0.57 mg/mg, uAPR showed sensitivity of 81.8% and specificity of 95.5%. At the cutoff value of 22.5%, %dRBC showed sensitivity of 54.5% and specificity of 86.4%. Conclusion: uAPR has higher sensitivity and specificity than %dRBC in differentiating glomerular from nonglomerular hematuria and can be used as a diagnostic tool. BIRDEM Med J 2022; 12(1): 51-56